Ответы и объяснения

prostomama1
Лексия
Лучший Ответ!
prostomama1

,,,,,,,,!,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,

5.0
1 оценка
1 оценка
Оцени!
Оцени!
можно вопрос? а почему мы под( г) 2дропь меняется ?
дробь *
Лексия

Г)  \frac{4}{x+3} -  \frac{5}{3-x} =  \frac{1}{x-3} -1  







 \frac{4}{x+3} +  \frac{5}{3+x} =  -\frac{1}{x+3} -1  

 \frac{9}{3+x}= -\frac{1-x-3}{3+x}  

9=-(1-x-3)
9=-1+x+3
9=x+2
x=7
д)  \frac{3}{x}+ \frac{4}{x-1} = \frac{5-x}{ x^{2} -x}  \\  \frac{3(x-1)+4x}{ x^{2} -x} =\frac{5-x}{ x^{2} -x} \\ 3x-3+4x=5-x \\ 3x+4x+x=3+5 \\ 8x=8 \\ x=1

е)  \frac{3y-2}{y} -  \frac{1}{y-2} =  \frac{3y+4}{ y^{2}-y}  \\  \frac{(3y-2)(y-2)-y}{y ^{2}-y } = \frac{3y+4}{ y^{2}-y} \\ 3 y^{2} -6y-2y+4-y=3y+4 \\ 
3y ^{2} -12y=0 \\ 3y(y-4)=0 \\ 
3y=0; y=0 \\ 
y-4=0;y=4
  

0.0
0 оценок
0 оценок
Оцени!
Оцени!